PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, KOMITMEN ORGANISASI TERHADAP MOTIVASI KERJA DAN KINERJA PEGAWAI BKD KLATEN - Arif Yunanto; Mulyanto . (ADVANCE, 2014)
This study aimsistoanalyzethe effect of(1)leadership style onwork motivation, (2)organizational culture onemployeesmotivation; (3) organization witha commitmenttoinfluenceemployeesmotivation, (4)leadership styleon employeesperformance; (5)organizational cultureon employeesperformance; (6)organizational commitmenton employeesperformance; (7)work motivation onemployee performance.The data usedin this studyweretaken with theprimarypopulationquestionnairesgiven toemployeesas many as 48people. Analysistoolsused inthetestinstrumentvalidity andreliability testing, analysisregressiontheintervening variable(Path Analysis), ttest, F test, testR2, correlation analysis, analysis of the effect. The test resultsshowedallinstrumentswere valid and reliable. The results showed : 1) Leadershipstylehada notsignificantpositive effectonwork motivation, 2) Organizational Culturehadsignificantpositive effectonwork motivation, 3) OrganizationalCommitmenthad positive and significant impactonwork motivation, 4) LeadershipStyleshad positive and significant effecton employees performance, 5) Organizational Culturehadsignificantnegative effecton employees performance, 6) Organizational commitmenthadsignificantpositive effecton employee performance, 7) Work Motivationhad positive and significant effecton Employee Performancein theRegional Employment Board ofKlaten.R-square value was 66.2% and a total, meaningful employee performance variation in Klaten Regional Employment Board, explained Leadership Style, Organizational Culture, Organizational Commitment to Work Motivation as intervening variable of 66.2% remaining 33.8% was explained as other variables outside the model instance variables of job satisfaction and employee discipline. Keywords: Leadership Style, Organizational Culture, Work Motivation, Employee performance.